Productivity Matters for Trade Policy : Theory and Evidence - Karacaovali, Baybars (World Bank, Washington, DC, 2012)
There is a growing literature that investigates the effect of trade liberalization on productivity. Nearly all such studies assume that trade policy is determined independently of productivity, hence it is exogenous. The author shows that this assumption is not valid in general, both theoretically and empirically, and that researchers may be underestimating the positive effect of liberalization on productivity when they do not account for the endogeneity bias. On the theory side, he demonstrates that under a standard political economy model of trade protection, productivity directly influences tariffs. Moreover, this productivity-tariff relationship partly determines the extent of liberalization across sectors even in the presence of a large exogenous unilateral liberalization shock that affects all sectors. The link between productivity and tariffs is maintained after the author includes in his political economy model a learning-by-doing motive of protection, which also serves as the source of liberalization. On the empirical side, he examines total factor productivity (TFP) estimates obtained at the firm level for Colombia between 1983 and 1998, and finds that more productive sectors receive more protection within this period. In estimating the effect of productivity on tariffs, he controls for the endogeneity of the two main right-hand-side variables-the inverse import penetration to import demand elasticity ratio and productivity-by using materials prices, the capital to output ratio, a measure of scale economies, and the TFP of the upstream industries as robust instruments. The author also accounts for the large trade liberalization between 1990 and 1992, and finds that the sectors with a higher productivity gain are liberalized less. Finally, he illustrates a system of equations estimation and shows that the positive impact of liberalization on productivity grows stronger when corrected for the endogeneity bias.